2016
DOI: 10.1080/17483107.2016.1222002
|View full text |Cite
|
Sign up to set email alerts
|

The validity of forceplate data as a measure of rapid and targeted volitional movements of the centre of mass in transtibial prosthesis users

Abstract: PostprintThis is the accepted version of a paper published in Disability and Rehabilitation: Assistive Technology. This paper has been peer-reviewed but does not include the final publisher proof-corrections or journal pagination. Citation for the original published paper (version of record):Rusaw, D. (2017) The validity of forceplate data as a measure of rapid and targeted volitional movements of the center of mass in transtibial prosthesis users. This research was conducted using using funds provided by The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 28 publications
1
14
1
1
Order By: Relevance
“…This has been achieved using test protocols such as the limits of stability (LOS) test, which assesses participants' ability to perform targeted volitional centre of mass (CoM) movements during upright posture. In addition, the LOS test has been validated for expressing volitional postural movement in prosthesis users 18 . These test protocols are important as they assess voluntary postural control and demand utilisation of the range of motion of the prosthetic ankle/foot componentry, reflecting the daily challenges faced by prosthesis users.…”
Section: Introductionmentioning
confidence: 99%
“…This has been achieved using test protocols such as the limits of stability (LOS) test, which assesses participants' ability to perform targeted volitional centre of mass (CoM) movements during upright posture. In addition, the LOS test has been validated for expressing volitional postural movement in prosthesis users 18 . These test protocols are important as they assess voluntary postural control and demand utilisation of the range of motion of the prosthetic ankle/foot componentry, reflecting the daily challenges faced by prosthesis users.…”
Section: Introductionmentioning
confidence: 99%
“…Often, these methods rely on extracting information about postural stability via displacement of the centre of pressure (CoP) [19]. Movement of the CoP as a model for movement of centre of mass (CoM) in TPUs has been validated in quiet standing [20] and during rapid movements in TPUs [21]. It has been shown that TPUs have larger adaptations following support surface perturbations resulting in larger displacements of CoP on the intact limb and controls when compared to the prosthetic side [9].…”
Section: Introductionmentioning
confidence: 99%
“…Studies that explicitly stated limitations or confounders were just over two-thirds of the total (Table 2),. 13,14,19–22,24,28–56,71,74,76,77,80–95,108,109,115–132,140–145,147–165,169–180,182–184,188–191,193–198 The most commonly mentioned limitation was small sample size, 20,22,24,28,29,32,33,35,37,39,40,42,45,47,52,54-57,74,80,82,86,87,89,93,95,109,118,119,121,123,126,129,141,143,145,148,149,154-159,161,164,169,172,183,198 followed by generalizability issues, 14,19-21,34,38,41,42,44,52-56,80,81,87,89,109,127-130,142,148,151,155,156,162,171,175-177,184,188,189,191,193,196 recall bias, 14,148,150,157,171,173,182,184 heterogeneous groups, 29,42,54,89,142,174,176,177 homogenous groups, 21,38,39,44,45,91,164 and convenience samples. 14,161,176,177,196…”
Section: Resultsmentioning
confidence: 99%